UJI PATOGENITAS Bacillus thuringiensis var. israelensis TERHADAP LARVA NYAMUK Aedes sp. SEBAGAI BIOKONTROL PENYEBAB PENYAKIT DEMAM BERDARAH DENGUE DI DENPASAR TAHUN 2014 - Hari Laksmi Santi; Sang Gede Purnama (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2016)
The Dengue Hemorrhagic Fever (DHF) in Indonesia increases every year. In 2008, cases of DHF in Indonesia accounted 137,469 cases (IR: 59.02 per 100,000 population, CFR 0.86%). This increased in 2009 to 154,855 DHF cases (IR: 66.48 per 100,000, CFR 0.89%). In 2010, Indonesia experienced the highest DHF case in ASEAN, namely 156,086 cases with 1,358 deaths (Kemenkes, 2011). Many preventive efforts had been carried out to eradicate Aedes sp. The bioinsecticide vector control using Bacillus thuringiensis is safe for the environment and humans compared to the synthetic insecticides. This study evaluated the pathogenicity of B. thuringiensis against larvae of Aedes sp. in Denpasar city. This study conducted Quasy Experimental Design of 6 treatments, concentrations of 50 µL, 40 µL, 30 µL, 20 µL, 10 µL and 1 control, with 4 repetitions. The number of cells and spores of B. thuringiensis used in this study was 11.2 x 109 cfu/ml and 7.43 x 109 cfu/ml, respectively. The highest mean score difference compared to the control was the 50 µL concentration with average larvae mortality at 6 hours of 96%, increasing to 100% in 12 and 24 hours. LC50 concentration within 6 hours was 4 µl/L, and LC90 concentration was 16 µl/L. Using statistical test, average mortality of larvae Aedes sp. at all concentrations were similar (p ? 0.005). The greater concentration of B. thuringiensis and the longer exposure time leads to a greater mortality of Aedes sp. larvae.